Are multifocal motor neuropathy patients underdiagnosed? An epidemiological survey in Japan. Issue 3 (11th December 2013) - Miyashiro, Ai; Matsui, Naoko; Shimatani, Yoshimitsu; Nodera, Hiroyuki; Izumi, Yuishin; Kuwabara, Satoshi; Imai, Tomihiro; Baba, Masayuki; Komori, Tetsuo; Sonoo, Masahiro; Mezaki, Takahiro; Kawamata, Jun; et al.
ABSTRACT Introduction: Our objective was to do an epidemiologic survey of patients with multifocal motor neuropathy (MMN) in comparison with those with amyotrophic lateral sclerosis (ALS) in Japan. Methods: In this retrospective study, we examined 46 patients with MMN and 1, 051 patients with ALS from major neuromuscular centers in Japan from 2005 to 2009. Diagnosis was based on the European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) and the revised El Escorial criteria. The efficacy of intravenous immunoglobulin (IVIg) was also taken into consideration in the diagnosis of MMN. Results: The ratio of MMN to ALS patients (0–0.10) varied among the centers, but mostly converged to 0.05. The prevalence was estimated to be 0.29 MMN patients and 6.63 ALS patients per 100, 000 population. Conclusions: The frequency of MMN patients was around 1 out of 20 ALS patients, and MMN was possibly underdiagnosed in some centers. Muscle Nerve49:357–361, 2014